Analysis of Resonance Response Performance of C-Band Antenna Using Parasitic Element - M. R. Zaman; M. T. Islam; N. Misran; J. S. Mandeep (The Scientific World Journal)
Analysis of the resonance response improvement of a planar C-band (4–8 GHz) antenna is proposed using parasitic element method. This parasitic element based method is validated for change in the active and parasitic antenna elements. A novel dual-band antenna for C-band application covering 5.7 GHz and 7.6 GHz is designed and fabricated. The antenna is composed of circular parasitic element with unequal microstrip lines at both sides and a rectangular partial ground plane. A fractional bandwidth of 13.5% has been achieved from 5.5 GHz to 6.3 GHz (WLAN band) for the lower band. The upper band covers from 7.1 GHz to 8 GHz with a fractional bandwidth of 12%. A gain of 6.4 dBi is achieved at the lower frequency and 4 dBi is achieved at the upper frequency. The VSWR of the antenna is less than 2 at the resonance frequency.